Provenance Variation on Early Survival Rate and Growth Performance of Oxytenanthera abyssinica (A. Rich.) Munro Seedlings at Green House: An Indigenous Lowland Bamboo Species in Ethiopia - Tinsae Bahru; Berhane Kidane; Yigardu Mulatu (International Journal of Forestry Research)
Background. Lowland Bamboo (O. abyssinica) is an indigenous multipurpose species in Ethiopia and endemic to Africa. Aims. The present study was aimed at investigating provenance variation on early survival rate and growth performance of O. abyssinica seedlings so as to obtain suitable provenance for production of high quality seedlings. Methods. Seeds were collected from Pawe and Sherkole districts. Following raise of seedlings data on survival count, culm height, root collar diameter (RCD), number of leaves, and biomass were recorded. Results. Pawe provenance had slightly higher survival rate (91%). Except seedlings RCD, rhizomes length, and roots fresh and dry weights, higher mean values of other morphological parameters were recorded in Sherkole provenance. Biomass of leaves and culms was higher in Shekole provenance, while root biomass was exceeded by the Pawe provenance. However, significant variations (P<0.05) between provenances were observed in RCD, rhizomes length, weight of fresh culms, and fresh and dry root system. Seedlings growth parameters (height and RCD) were positively and significantly correlated with Biomass variables and hence could be considered as better evaluation criteria for seedling quality at green house. Conclusion. Sherkole provenance should be considered for raising O. abyssinica seedlings at green house.